Tpl2 Ablation Leads to Hypercytokinemia and Excessive Cellular Infiltration to the Lungs During Late Stages of Influenza Infection - Latha, Krishna; Jamison, Katelyn F.; Watford, Wendy T. (Frontiers in Immunology, 2021)
Tumor progression locus 2 (Tpl2) is a serine-threonine kinase known to promote inflammation in response to various pathogen-associated molecular patterns (PAMPs), inflammatory cytokines and G-protein-coupled receptors and consequently aids in host resistance to pathogens. We have recently shown that Tpl2-/- mice succumb to infection with a low-pathogenicity strain of influenza (x31, H3N2) by an unknown mechanism. In this study, we sought to characterize the cytokine and immune cell profile of influenza-infected Tpl2-/- mice to gain insight into its host protective effects. Although Tpl2-/- mice display modestly impaired viral control, no virus was observed in the lungs of Tpl2-/- mice on the day of peak morbidity and mortality suggesting that morbidity is not due to virus cytopathic effects but rather to an overactive antiviral immune response. Indeed, increased levels of interferon-β (IFN-β), the IFN-inducible monocyte chemoattractant protein-1 (MCP-1, CCL2), Macrophage inflammatory protein 1 alpha (MIP-1α; CCL3), MIP-1β (CCL4), RANTES (CCL5), IP-10 (CXCL10) and Interferon-g (IFN-g) was observed in the lungs of influenza-infected Tpl2-/- mice at 7 days post infection (dpi). Elevated cytokine and chemokines were accompanied by increased infiltration of the lungs with inflammatory monocytes and neutrophils. Additionally, we noted that increased IFN-β correlated with increased CCL2, CXCL1 and nitric oxide synthase (NOS2) expression in the lungs, which has been associated with severe influenza infections. Bone marrow chimeras with Tpl2 ablation localized to radioresistent cells confirmed that Tpl2 functions, at least in part, within radioresistent cells to limit pro-inflammatory response to viral infection. Collectively, this study suggests that Tpl2 tempers inflammation during influenza infection by constraining the production of interferons and chemokines which are known to promote the recruitment of detrimental inflammatory monocytes and neutrophils.